Dynamic of indices of lipid peroxidation and antioxidant protection in muscular tissue and blood serum of rats with acute ischemia-reperfusion - Televiak, A. T.; Veresiuk, T. O.; Selskyy, P. R.; Volska, A. S.; Kurylo, K. I.; Nebesna, Z. M.; Datsko, T. V.; Boymystruk, I. I. (Journal of Education, Health and Sport, 2018)
Acute limb ischemia occurs as a result of sudden decrease in its perfusion, which usually occurs during the obturation of the lumen of large arteries due to acute thrombosis or embolism either impaired of vascular patency caused by trauma or compression (including the application of hemostatic tourniquets). In the case of restoration of blood supply to previously ischemic tissues, there is an ischemic-reperfusion syndrome, in which one of the main pathogenetic links of tissue alteration is the activation of lipid peroxidation. The content of diene conjugates, triene conjugates, TBA-active products, superoxide dismutase and catalase in homogenate of the muscle tissue and blood serum of 30 white rats under condition of experimental acute ischemia was determined. Acute ischemia was caused by the application of SWAT (Stretch-Wrap-And-Tuck) rubber bundles on the hind limbs of the animals for 2 hours. It was experimentally found that the maximum increase in the content of diene and triene conjugates in the injured muscle tissue of the animals occurred in the early post-ischemic period on the 2nd hour of reperfusion with a decreaseing on the 1st and 7th day and the subsequent return of indicators in the late postischemic period on the 14th day to the level of control group. The increasing of TBA-active products in the muscle tissue occurred in the first three groups of the rats and peaked in the third group (reperfusion for the 1st day), after which their level decreased in the animals during the late reperfusion period, reaching in the last group on the 14th day of reperfusion indices, close to the values of the control group. The dynamics of activity of superoxide dismutase and catalase in the muscle homogenate were to a large extent similar (as indicated by the strong positive correlation (+0,99) between them), gradually increasing and reaching the maximum on 7th day of the ischemia-reperfusion symdrome. As a result of the experiment, a decreasing in the antioxidant-prooxidant index in all experimental groups of the rats was also observed in the muscle homogenate, which was the most pronounced on the 1st day of ischemia-reperfusion. The comparative analysis of the similar parameters of lipid peroxidation and antioxidant protection in the muscle homogenate and blood serum showed a direct correlation in all the studied pairs. The strong and moderate positive correlation between analogous indices of LPO and AOP in muscle homogenate and blood serum in all five studied pairs indicates similar changes of these indicators at the local and systemic levels.